UPAYA PENINGKATAN SENSITIVITAS NANOPARTIKEL PERAK UNTUK ANALISIS ION MERKURI(II) SECARA CITRA DIGITAL DENGAN PENAMBAHAN NaCl - Edo Prasetia; M. Lutfi Firdaus; Elvinawati Elvinawati (University of Bengkulu, 2019)
The very small concentration of mercury (Hg) in the environment is difficult to detect, so an accurate and sensitive method is needed in order to detect the concentration. Therefore, the purpose of this study was to develop an accurate and sensitive method based on the use of digital imaging methods and silver nanoparticles (AgNPs) as colorimetric sensors for mercury(II) ions (Hg2+) analysis. The process of making AgNPS is done by a bottom up method involving a reduction reaction. The precursor used is 1 mM AgNO3 solution and as bioreductor is an antioxidant compound present in extract of chili pepper (Capsicum frutescens L) with ratio 1: 9. Contact time variation 15, 30, 45, 60 min and 1, 2, 7 days. Addition of NaCl 0.5 and 1 M NaCl were used to increase the sensitivity of AgNPs as colorimetric sensors of Hg2+ ions. Digital Image Method is used to analyze Hg2+ ions at ppb concentration level. The results of the most optimum silver nanoparticles synthesized at the time of solar heating is 60 minutes. The addition of NaCl 0.5 M and 1 M into AgNPs is able to increase the sensitivity of AgNPs. Limit of Detection (LoD) of AgNPs added NaCl 0.5 M and 1 M was able to detect Hg2 + ions by 3.02 ppb and 2.46ppb.